Improved CPD based DOA estimation of nested array - Sibei CHENG; Xiao LUO; Bochou JIANG; Yuting WANG; Huanyu WU (Dianxin kexue)
In order to avoid searching the peak value in space domain, when estimating nested array’s the direction of direction of arrival(DOA), the canonical polyadic decomposition(CPD) was applied into the nested array, namely using the one time singular value decomposition(SVD), bilinear mapping and tensor decomposition to obtain the steering vector matrix and arrival angle.However, the existing CPD algorithm only can be applied in noiseless environment, the algorithm was improved by utilizing SVD two times, and was made to be applied in both noiseless and noisy environments.The simulation results demonstrate that in the same signal to noise ratio(SNR) and snapshot, the DOA estimation algorithm of nested array based on the improved CPD has better performances and less running time than the MUSIC and space smoothing algorithms.